Theoretical study of the geometric and electronic characterization of carbendazim-based drug (Nocodazole). Issue 6 (June 2020) - Khattab, Muhammad
Abstract: Scarcity in studies defining the precise three-dimensional structure of approved drugs has led to an abandoning of their use for other therapeutic indications. In this manuscript, we solely focus on studying computationally the anticancer drug "Nocodazole" as a model compound for anthelmintic drugs –due to structural similarity– proven to exert anticancer activity such as Mebendazole and Albendazole. Computations on Nocodazole structures deposited in the Protein Data Bank (PDB) revealed possible existence of at least 6 conformers of Nocodazole. By combining the reported experimental UV-Vis data with our calculations, two conformers were assigned as the predominant structures of Nocodazole. In addition, td-DFT calculations revealed that the conformational flexibility of Nocodazole results in significant changes in atomic and molecular charge densities. The results have ramifications in identification of possible conformers of carbendazim-based drugs for repurposing in oncology through giving deep insights in understanding the spatial and electronic changes upon drug binding to anticancer targets. Abstract : Physical chemistry; Theoretical chemistry; Pharmaceutical chemistry, Drug repurposing; DFT calculation; Benzimidazole carbamates